(untitled) - Osada, Takashi (Japan, 1991)
The first step in any quality movement should be a 5S movement - that is, a determination to organize the workplace, keep it neat and clean, maintain standardized conditions, and maintain the discipline needed to do a good job. By using this book to initiate a 5S movement, your company will see results in: higher productivity and better quality; improved accident prevention; employees taking pride in their work; healthier corporate climate.
Keywords: Quản lý chất lượng toàn diện,Total quality management; Nhật Bản,Japan